A PCR assay to quantify patterns of HBV transcription. (17th March 2021) - D'Arienzo, Valentina; Magri, Andrea; Harris, James M.; Wing, Peter A. C.; Ko, Chunkyu; Rubio, Claudia Orbegozo; Revill, Peter A.; Protzer, Ulrike; Balfe, Peter; McKeating, Jane A.
Abstract : Hepatitis B virus (HBV) is the prototype member of the family Hepadnaviridae and replicates via episomal copies of a covalently closed circular DNA (cccDNA) genome of approximately 3.2 kb. The chromatinization of this small viral genome, with overlapping open reading frames and regulatory elements, suggests an important role for epigenetic pathways to regulate HBV transcription. However, the host pathways that regulate HBV transcription and the temporal nature of promoter usage in infected cells are not well understood, in part due to the compact genome structure and overlapping open reading frames. To address this we developed a simple and cost-effective PCR assay to quantify the major viral RNAs and validated this technique using current state-of-art de novo HBV infection model systems. Our PCR method is three orders of magnitude more sensitive than Northern blot and requires relatively small amounts of starting material, making this an attractive tool for assessing HBV transcription.